Water-soluble Dietary Fibers and Cardiovascular Diseases: A Comprehensive Review - Patience, Obi Olor; Archibong, James E (Contemporary Research and Perspectives in Biological Science Vol. 4, 2024)
The purpose of this study was to critically review the cardio-protective potential of diets and foods rich in soluble fiber. Fibre is found in plant-based food products like rye, wholegrain wheat, fruits, oats, nuts, legumes, and vegetables. Consuming fiber as well as wholegrain foods has been linked to various health benefits such as; a reduced risk of being overweight or obese, a low risk of developing type 2 diabetes, cardiovascular diseases as well as a lesser risk of bowel cancer. The study critically reviewed concepts such as soluble fiber and Cardiovascular Diseases, other benefits of functional Foods in the Hypercholesterolemia Family, Isoflavones, \(β\) –glucan, and Fatty Acids. The study adopted the descriptive method in analyzing issues relating to the cardio-protective potentials of diets. The diet must be based on increasing the amount of mono- and polyunsaturated fatty acids, then reducing the consumption of saturated fatty acids, trans fat, and weight loss when required. Physical exercise should be encouraged mainly aerobic exercise, since exercise increases the concentration of HDL-C, reduced concentrations of triglycerides, and aids in weight loss. They emphasized that patients with familial hypercholesterolemia should not start any physical activity without evaluation and accompanied cardiogram. In general, there is a need for more studies on familial hypercholesterolemia. Studies that relate to genetic disease and patient adherence to dietary treatment are unique for checking the concentrations of both total cholesterol, and LDL-C, and possibly to confirm the efficacy of isolated nutritional treatment, i.e. without the need for pharmacological treatment. The study recommended that dietary treatment should be accompanied by a professional nutritionist, for better grip and results to treatment. The dietary intervention alone is not enough to treat familial hypercholesterolemia, but it should always be the first measure implemented.